A Juridical Review of Cybercrime and Defamation under Indonesia’s Law No. 1 of 2024 on Electronic Information and Transactions - Adi Darmawansyah; Andry Dwiarnanto; Irwan Putra Satriyawan; Istiqomah (Penerbit Mandalika Indonesia, 2025)
Along with technological advances, social changes will also be affected, one of which is crime in cyber crime. Existing society will always coexist with cyberspace and there are even criminal law problems in it (cybercrime). The research analyzes the provisions of criminal acts of defamation through cybercrime which are according to the provisions of positive law in Indonesia. And how the law can accommodate the position of evidence in cyberspace. Normative juridical research specifically discusses regulations in accordance with Law of the Republic of Indonesia Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning Information and Electronic Transactions. Defamation in cyber crimes is regulated in the Criminal Code Articles 310 to 321 and is also regulated in Law Number 1 of 2024, Second Amendment to Law Number I1 of 2008 concerning Information and Electronic Transactions Article 27A and Article 27 B paragraph (2) Jo. Article45. The newNational Criminal Code(KUHP) also regulates provisions for defamation in relation to cybercrime. Proof of criminal acts of information and electronic transactions based on Law Number 1 of 2024, Second Amendment to Law Number I1 of 2008 Regarding ITE, it is based on valid evidence as regulated in Article 184 of the Criminal Procedure Code.